Archaeosome Adjuvant Overcomes Tolerance to Tumor-Associated Melanoma Antigens Inducing Protective CD8+ T Cell Responses. (26th December 2010) - Krishnan, Lakshmi; Deschatelets, Lise; Stark, Felicity C.; Gurnani, Komal; Sprott, G. Dennis
Abstract : Vesicles comprised of the ether glycerolipids of the archaeon Methanobrevibacter smithii (archaeosomes) are potent adjuvants for evoking CD8 + T cell responses. We therefore explored the ability of archaeosomes to overcome immunologic tolerance to self-antigens. Priming and boosting of mice with archaeosome-antigen evoked comparable CD8 + T cell response and tumor protection to an alternate boosting strategy utilizing live bacterial vectors for antigen delivery. Vaccination with melanoma antigenic peptides TRP181-189 and Gp10025-33 delivered in archaeosomes resulted in IFN- γ producing antigen-specific CD8 + T cells with strong cytolytic capability and protection against subcutaneous B16 melanoma. Targeting responses against multiple antigens afforded prolonged median survival against melanoma challenge. Entrapment of multiple peptides within the same vesicle or admixed formulations were both effective at evoking CD8 + T cells against each antigen. Melanoma-antigen archaeosome formulations also afforded therapeutic protection against established B16 tumors when combined with depletion of T-regulatory cells. Overall, we demonstrate that archaeosome adjuvants constitute an effective choice for formulating cancer vaccines.